2020
DOI: 10.1186/s12883-020-01953-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rTMS on Parkinson’s cognitive function: a systematic review and meta-analysis

Abstract: Background To evaluate the effects and optimal parameters of repetitive transcranial magnetic stimulation (rTMS) on cognition function of patients with Parkinson’s disease (PD) and to estimate which cognitive function may obtain more benefits from rTMS. Method The articles dealing with rTMS on cognitive function of PD patients were retrieved from the databases until April 2019. Outcomes of global cognitive function and different cognitive domains were extracted. The standardized mean differences (SMDs) with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 70 publications
5
22
0
Order By: Relevance
“…A greater number of treatment sessions is associated with better SE and sleep quality as measured by PSQI, and a greater number of pulses per session is associated with an improved PSQI. These findings are consistent with many previous studies among people with other mental disorders (93)(94)(95)(96)(97). Meanwhile, the inverse associations between the length of treatment per session and TST and PSQI are also noteworthy.…”
Section: Discussionsupporting
confidence: 92%
“…A greater number of treatment sessions is associated with better SE and sleep quality as measured by PSQI, and a greater number of pulses per session is associated with an improved PSQI. These findings are consistent with many previous studies among people with other mental disorders (93)(94)(95)(96)(97). Meanwhile, the inverse associations between the length of treatment per session and TST and PSQI are also noteworthy.…”
Section: Discussionsupporting
confidence: 92%
“…This is very encouraging, given that AD and dementias share several common elements with these disorders, such as their pathogenetic mechanisms [77,78]. Additionally, these diseases are known for their cognitive sequelae [79,80], and rTMS has been explored as a treatment modality for cognitive decline in this context as well [5,72]. As such, rTMS's efficacy in this setting raises hopes for its application in dementia as well.…”
Section: Discussionmentioning
confidence: 91%
“…RTMS has been extensively studied in the context of PD, and a recent meta-analysis on the effects of rTMS on the cognitive performance of PD patients reported that HF-rTMS over the DLPFC may indeed be beneficial [72]. Due to the similarities between LBD and PD, and the existing literature and evidence on rTMS's efficacy on psychiatric disorders [73], it has long been hypothesized that rTMS could also be a therapeutic option for LBD [71].…”
Section: Lewy Body Dementiamentioning
confidence: 99%
“…Recent evidence suggests the efficacy of rTMS in improving response inhibition in Parkinson’s disease when applied over the dorsolateral prefrontal cortex 100 . Yet, to our best knowledge, no studies have targeted the pre-SMA with aim modifying cognitive control in Parkinson’s disease with or without ICDs.…”
Section: Discussionmentioning
confidence: 99%